1989
DOI: 10.1007/bf00001283
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dissolved oxygen and aquatic surface respiration on the critical thermal maxima of three intermittent-stream fishes

Abstract: SynopsisCritical thermal maxima (CTM) were determined for three species of fish in hypoxic (1.2 mg I-]), normoxic (7 mg I-') and hyperoxic (12 mg I-') oxygen tensions. All fish were acclimated to 30°C under a regulated photoperiod of 12:12. During each CTM determination, one-half of the test fish were allowed free access to the surface (to permit aquatic surface respiration) while the remaining one-half were denied access to the surface. Under hypoxic conditions, CTMs of Fundulus notatus, Notropis lutrensis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…The present study bridges these earlier studies, and confirms their findings, by showing an uncoupling of AS and CT max when fish are exposed to environmental (ambient) hypoxia. Our findings are also supported by previous studies which have reported reduced CT max under severe hypoxia (Weatherley, 1970;Rutledge and Beitinger, 1989;Ellis et al, 2013;Healy and Schulte, 2012) and maintained CT max under moderate hypoxia (Weatherley, 1970;Ellis et al, 2013). However, direct comparisons with our results are difficult because these studies only measured CT max at one (Rutledge and Beitinger, 1989;Healy and Schulte, 2012) or two (Weatherley, 1970;Ellis et al, 2013) levels of hypoxia, applied extremely high rates of temperature increase (18-90°C h −1 ; Weatherley, 1970;Rutledge and Beitinger, 1989;Healy and Schulte, 2012), allowed Pw O2 to drift from normoxia to hypoxia during measurements (Ellis et al, 2013), or were performed on an air-breathing species with surface access (Rutledge and Beitinger, 1989).…”
Section: Discussionsupporting
confidence: 92%
“…The present study bridges these earlier studies, and confirms their findings, by showing an uncoupling of AS and CT max when fish are exposed to environmental (ambient) hypoxia. Our findings are also supported by previous studies which have reported reduced CT max under severe hypoxia (Weatherley, 1970;Rutledge and Beitinger, 1989;Ellis et al, 2013;Healy and Schulte, 2012) and maintained CT max under moderate hypoxia (Weatherley, 1970;Ellis et al, 2013). However, direct comparisons with our results are difficult because these studies only measured CT max at one (Rutledge and Beitinger, 1989;Healy and Schulte, 2012) or two (Weatherley, 1970;Ellis et al, 2013) levels of hypoxia, applied extremely high rates of temperature increase (18-90°C h −1 ; Weatherley, 1970;Rutledge and Beitinger, 1989;Healy and Schulte, 2012), allowed Pw O2 to drift from normoxia to hypoxia during measurements (Ellis et al, 2013), or were performed on an air-breathing species with surface access (Rutledge and Beitinger, 1989).…”
Section: Discussionsupporting
confidence: 92%
“…However, this substantial increase in AS under hyperoxia did not enhance the acute upper thermal limits of perch, as CT max was not significantly elevated when compared with control fish. Although these findings conflict with a study investigating the effects of increased environmental oxygen tension on acute thermal tolerance of goldfish (Carassius auratus) at hyperbaric pressures (Weatherley, 1970), they are consistent with findings from a range of other fish species exposed to hyperoxic conditions under ambient pressure (Healy and Schulte, 2012;Mark et al, 2002;Rutledge and Beitinger, 1989). Weatherley (1970) also observed that even in the presence of a superabundance of oxygen, enhanced thermal tolerance ended abruptly at a definite 'breakpoint' and thus was indicative of a physiological failure independent of oxygen limitation.…”
Section: Hyperoxia Increases Aerobic Scope But Not Acute Upper Thermasupporting
confidence: 64%
“…hypoxia; Healy and Schulte, 2012;Rutledge and Beitinger, 1989;Weatherley, 1970). While these results lend support to the idea that oxygen supply limits thermal tolerance, one would expect hyperoxia (i.e.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…To establish causality requires showing that tissue hypoxia occurs at the onset of other adverse effects of temperature and that experimentally manipulating tissue hypoxia levels (e.g. through experimental hyperoxia) improves thermal tolerance in fishes (Weatherley, 1970;Rutledge and Beitinger, 1989).…”
Section: Ecological Relevance Of Aerobic Scope and T Optasmentioning
confidence: 99%